THE IMPACT OF STRENGTHS USE IN THE WORKPLACE TO THE DEVELOPMENT OF POSITIVE PSYCHOLOGICAL CAPITAL (PSYCAP) - Setyobudi, Wahyu T (Research Center and Case Clearing House PPM School of Management, 2011)
The positive psychology and positive organizational behavior approach has grown rapidly in the last decade. This research was designed to find the relationship between strengths use and psychological capital (PsyCap). Survey questionnaires are administered to Indonesian employee, most of them in managerial level. After that, several simple regression procedures are performed. The main finding is that the strengths used among Indonesian manager is low. The low score can be attributable to the mindset dimension of strengths use. Other finding is that, although have a positive significant correlation coefficients with PsyCap, the strengths use in the workplace is a weak predictor of PsyCap. Some discussions about the findings and managerial implication is presented.